Nanozyme conjugated chitosan nanoparticles improve buffalo bull sperm cryopreservation by enhancing antioxidant defense and mitochondrial function - Sindi, Ramya Ahmad; Alfattah, Mohammed A.; Hassan, Mahmoud A. E.; El-Haroun, Ehab; Noredlin, Ahmed E.; Abdelnour, Sameh A.; Moussa, Mahmoud (Frontiers in Veterinary Science, 2025)
IntroductionCryopreservation is commonly used to preserve fertility and support genetic improvement in livestock. However, it often compromises sperm function and quality due to the excessive generation of oxidative stress. Nanozymes, a cutting-edge development in nanotechnology, offer a versatile and promising tool for mitigating oxidative stress caused by cryo-injury. This study targeted to assess the protective effects of selenium conjugated chitosan nanoparticles (SeCN; as a nanozyme) when added to semen freezing extenders in buffalo bulls.MethodsSemen samples were extended with 0 (SeCN0), 0.5 (SeCN0.5), 1 (SeCN1), or 2 (SeCN2) μg/mL SeCN, frozen at −196 °C, and assessed post-thaw for sperm quality, antioxidant status, mitochondrial activity and ultrastructural changes.ResultsThe SeCN supplementation significantly improved all post-thawed sperm parameters in a dose-dependent manner (p < 0.001). A significant linear increase (p < 0.01) was monitored in viability, sperm progressive motility, and plasma membrane integrity with increasing concentrations of SeCN supplementation. The SeCN2 group showed the highest percentages of sperm progressive motility, plasma membrane integrity, and viability related to SeCN groups (p < 0.05). Sperm abnormalities decreased linearly with SeCN supplementation, reaching the lowest rate in the SeCN2 group (p < 0.01 compared to other groups). Chromatin damage decreased significantly in a cubic manner in the SeCN1 and SeCN2 groups compared to the other groups (p < 0.01). For antioxidant status, the analysis showed a clear linear increase in both superoxide dismutase (SOD) levels and total antioxidant capacity (TAC) levels (p < 0.01). The SeCN2 group exhibited the highest SOD activity, while the SeCN1 and SeCN2 groups showed the highest TAC values (p < 0.01) compared to other groups. Additionally, glutathione peroxidase (GPx) activity in all SeCN-supplemented groups demonstrated a cubic increase (p < 0.01) compared to the control group. The SeCN2 group showed the most effective reduction in MDA levels, followed by the SeCN1 and SeCN0.5 groups (p < 0.001). Nitric oxide was significantly decreased in a linear manner by the addition of SeCN (p < 0.001). A significant cubic increase in mitochondrial membrane potential (MMP) was observed, with the addition of 1 or 2 μg of SeCN/mL (p < 0.001). Ultrastructural analysis via transmission electron microscopy confirmed improved preservation of acrosomal, mitochondrial, and plasma membrane integrity of buffalo spermatozoa.DiscussionAt a concentration of 1 or 2 μg/mL, SeCN demonstrates potent cryoprotective effects by enhancing sperm function, reducing oxidative stress, and preserving mitochondrial activity and ultrastructure changes of sperm. Incorporating SeCN into semen extenders may improve cryosurvival in buffalo and represents a promising strategy for optimizing artificial insemination outcomes in livestock breeding programs.